Where we live - Hoe, Susan (Pleasantville, NY : Gareth Stevens Pub., 2009)
Explains what maps are and why they are important, looks at how maps can be used to provide information about where people live, and includes an activity.
What is a map? -- Why do we need maps? -- Mapping your bedroom -- Mapping your town -- Using your town map -- Mapping your country -- Mapping the world -- Mapping a country in Africa: Sudan -- Mapping Grace's village -- Measuring for maps -- Mapping with computers -- Mapping African animals -- Making a playground map.
Includes index.
3.8
3-6
Keywords: Cartography -- Juvenile literature; Maps -- Juvenile literature; Cartography; Maps; Map drawing; Maps